Нові для фауни України види черепашкових амеб (Rhizopoda, Testacealobosea, Nebelidae) - Алпатова, Оксана; Alpatova, Oksana (Східноєвропейський національний університет імені Лесі Українки, 2015)
Наведено відомості про знаходження у водоймах Житомирського Полісся трьох нових для фауни України видів черепашкових амеб: Nebela bigibbosa Penard, 1890, N. dentistoma Penard, 1890, N. vitraeа Penard, 1899; подано їхні переописи та короткі екологічні характеристики. Видові нариси виконано на основі власних спостережень з урахуванням літературних даних. The genus Nebela Leidy, 1874 is one of the well-studied genera of the testaceans. More than 120 taxa of this genus Nebela have been described until now. Most of them are cosmopolitan and inhabiting in sphagnums and soils. The one of the most perspective territories of Ukraine for the freshwater protists study is Ukrainian Polissya with different type of water reservoirs. Thus purposeful ekologic-faunistic research of testaceans of Zhitomir Polessya is not conducted, what coused the special researches of this group for a region. There are found of 3 species of testate amoebae new for Ukraine: Nebela bigibbosa Penard, 1890, N. dentistoma Penard, 1890, N. vitraeа Penard, 1899. The arcticle contains the original descriptions and short ecological descriptions feature of investigated taxa. Species descriptions are written on the basis of own observation and publiched data.
The New Species of Testate Amoebae for the Fauna of Ukraine (Rhizopoda, Testacealobosea, Nebelidae)
Keywords: таксон; черепашкові амеби; Nebela; фауна; сфагнум; Житомирське Полісся; taxa; testate amoebae; Nebela; fauna; sphagnum; Zhytomir Polessje